2021
DOI: 10.3934/publichealth.2022015
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an outdoor loose parts intervention on Nova Scotia preschoolers' fundamental movement skills: a multi-methods randomized controlled trial

Abstract: <abstract> <p>Development of fundamental movement skills in early childhood supports lifelong health. The potential for outdoor play with loose parts to enhance fundamental movement skills has not been investigated. A multi-methods randomized controlled design was used to determine the efficacy of integrating outdoor loose parts play into Nova Scotia childcare centers (19 sites: 11 interventions, 8 control). Movement skills (n = 209, age 3–5 years) were assessed over a 6-month period to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…There is an increase in students' motor competency achievement through field games because students get the opportunity to combine/repeat movements and take risks (Branje et al, 2022), develop skills (Barba-Martín et al, 2020), increase enjoyment so as to be able to motivate students in learning student movement skills (Jia, 2021;Vasileva-Stojanovska et al, 2015;Gil-Arias et al, 2021). This shows that the use of field games can be used to stimulate students' motor competence.…”
Section: Discussionmentioning
confidence: 99%
“…There is an increase in students' motor competency achievement through field games because students get the opportunity to combine/repeat movements and take risks (Branje et al, 2022), develop skills (Barba-Martín et al, 2020), increase enjoyment so as to be able to motivate students in learning student movement skills (Jia, 2021;Vasileva-Stojanovska et al, 2015;Gil-Arias et al, 2021). This shows that the use of field games can be used to stimulate students' motor competence.…”
Section: Discussionmentioning
confidence: 99%
“…This study will apply the balance assessment of PGMQS, a validated tool for use in 3-year-olds that assesses four components of balance: single leg standing, tandem standing, walking line forward, and walking line backward [ 52 ]. This tool has previously been used to investigate balance development in preschoolers taking part in an outdoor loose parts intervention in Nova Scotia [ 55 ]. One child will be assessed at a time; the researcher will demonstrate how to correctly perform the task and then ask the child to perform the task.…”
Section: Methodsmentioning
confidence: 99%
“…We recently reported that there was a non-intervention effect on quantitative measures of preschoolers’ fundamental movement skills; however, educators spoke about how outdoor loose parts play provided opportunities for children to combine and repeat movements, and take risks, supporting physical, cognitive and socio-emotional development [ 19 ]. While some results of the PLEY project have been published [ 19 22 ], we have not yet examined if participating in the PLEY intervention was associated with increased physical literacy, as hypothesized.…”
Section: Introductionmentioning
confidence: 99%
“…The objective of this study is to explore the role of the PLEY project on Nova Scotian preschoolers’ domains of physical literacy (physical activity, physical competence, confidence and motivation, knowledge and understanding) using mixed-methods. A mixed-method approach allows us to build on previous reports of quantitative findings [ 19 , 23 ] and provide further insight into how outdoor loose parts play (OLPP) in the PLEY project contributes to the development of physical literacy. In this study, physical literacy was conceptualized based on the International Physical Literacy Association’s definition that includes physical, affective, motivational and behavioural domains and has also been endorsed as Canada’s Consensus Statement on Physical Literacy [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%